Venetoclax plus azacitidine in Japanese patients with untreated acute myeloid leukemia ineligible for intensive chemotherapy. (5th November 2021) - Yamamoto, Kazuhito; Shinagawa, Atsushi; DiNardo, Courtney D; Pratz, Keith W; Ishizawa, Kenichi; Miyamoto, Toshihiro; Komatsu, Norio; Nakashima, Yasuhiro; Yoshida, Chikashi; Fukuhara, Noriko; Usuki, Kensuke; Yamauchi, Takahiro; et al.
Abstract: Background: The phase 3 VIALE-A trial (NCT02993523) reported that venetoclax-azacitidine significantly prolonged overall survival compared with placebo-azacitidine in patients with newly diagnosed acute myeloid leukemia ineligible for intensive chemotherapy. Herein, efficacy and safety of venetoclax-azacitidine are analyzed in the Japanese subgroup of VIALE-A patients. Methods: Eligible Japanese patients were randomized 2:1 to venetoclax-azacitidine ( N  = 24) or placebo-azacitidine ( N  = 13). Primary endpoints for Japan were overall survival and complete response (CR) + CR with incomplete hematologic recovery (CRi). Venetoclax (target dose 400 mg) was given orally once daily. Azacitidine (75 mg/m 2 ) was administered subcutaneously or intravenously on Days 1–7 of each 28-day cycle. Results: Median follow-up was 16.3 months (range, 1.0–20.3). Median overall survival was not reached with venetoclax-azacitidine (hazard ratio 0.409 and 95% confidence interval: 0.151, 1.109); overall survival estimate was higher with venetoclax-azacitidine than placebo-azacitidine at 12 (67 and 46%) and 18 months (57 and 31%), respectively. CR and CRi rates were 67% with venetoclax-azacitidine and 15% with placebo-azacitidine. Most common any-grade adverse events were febrile neutropenia (79 and 39%), thrombocytopenia (54 and 77%), constipation (54 and 54%) and decreased appetite (54 and 38%) in the venetoclax-azacitidine and placebo-azacitidine arms, respectively. Only 1 patient in the venetoclax-azacitidine arm, and no patients in the placebo-azacitidine arm, had grade 4 febrile neutropenia that led to treatment discontinuation. Conclusions: This Japanese subgroup analysis of VIALE-A demonstrates comparable safety and efficacy outcomes compared with the global study and supports venetoclax-azacitidine as first-line standard-of-care for Japanese treatment-naive patients with acute myeloid leukemia who are ineligible for intensive chemotherapy. Abstract : Venetoclax-azacitidine was well tolerated in the Japanese subgroup of VIALE-A ( N  = 37) and showed improved efficacy versus placebo-azacitidine in patients with acute myeloid leukemia ineligible for intensive chemotherapy, supporting use as first-line standard-of-care.